Functional Mitral Regurgitation and the Role of Transcatheter Repair - Richa Gupta, MD, MPH; Holly Gonzales, MD; Stacy Tsai, MD; Angela Lowenstern, MD; JoAnn Lindenfeld, MD (Structural Heart, 2025)
Secondary mitral regurgitation (SMR), classified as ventricular or atrial SMR, is associated with excess mortality, heart failure (HF) hospitalization, and worsening quality of life. Therapy is directed toward the underlying cardiomyopathy first with use of neurohormonal antagonism, cardiac resynchronization therapy and arrhythmia reduction, which can reduce MR severity and improve outcomes, followed by transcatheter therapies. Multimodality imaging in the evaluation of MR is critical to determine the mechanism, severity, and options for intervention. Transcatheter treatment of severe SMR provides a percutaneous option for patients who remain symptomatic despite optimal medical management, and there have been significant advances in the procedural capabilities and devices available for treatment. The Cardiovascular Outcomes Assessment of the MitraClip Percutaneous Therapy for Heart Failure trial demonstrated improvement in morbidity and mortality with use of mitral transcatheter edge-to-edge repair (mTEER). The results of this trial suggest that greater proportionate MR, in which the magnitude of MR is accompanied proportionately with a high degree of LV dilation, confers less clinical benefit. A window of opportunity exists during which time mTEER may improve symptoms and prognosis in HF patients as guided by Cardiovascular Outcomes Assessment of the MitraClip Percutaneous Therapy for Heart Failure criteria in stage C HF. This review describes our current understanding of the pathophysiology and treatment of SMR. Additionally, it explores several questions as to the optimal timing of transcatheter intervention, the role of mTEER in moderate MR, our understanding of exercise-induced MR, implications for mitral valvular and ventricular remodeling, and whether mTEER may facilitate optimization of medical therapy.